2021
DOI: 10.1002/cyto.b.22040
|View full text |Cite
|
Sign up to set email alerts
|

Use of flow cytometry and cytology to differentiate breast implant‐associated anaplastic large cell lymphoma from reactive seromas in Brazilian patients

Abstract: Introduction:The combination of cytology and multiparametric flow cytometry (MFC) may be useful in the diagnosis of breast implant-associated anaplastic large cell lymphoma (BIA-ALCL) and may be a practical way to differentiate lymphoma from benign and reactive seromas. Although the Brazilian breast implant market is the second largest in the world, with several manufacturers and the almost exclusive use of textured implants, the occurrence of BIA-ALCL in Brazil is underreported. Methods: One hundred seventeen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 13 publications
(21 reference statements)
3
13
0
Order By: Relevance
“… 29 Our case showed similar findings, the malignant cells exhibiting strong CD30, CD45, CD4, and CD2 expression, negative for CD5 and low positive expression of CD3, CD7, and CD8. In other reported case series, the neoplastic CD30-positive cells were found to co-express CD25 and HLA-DR, 27 , 31 a finding also present in our case.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“… 29 Our case showed similar findings, the malignant cells exhibiting strong CD30, CD45, CD4, and CD2 expression, negative for CD5 and low positive expression of CD3, CD7, and CD8. In other reported case series, the neoplastic CD30-positive cells were found to co-express CD25 and HLA-DR, 27 , 31 a finding also present in our case.…”
Section: Discussionsupporting
confidence: 87%
“… 16 More recently, various groups are assessing the role of flow cytometry analyses in the initial diagnosis and evaluation of breast implant-associated ALCL. 27 31 Romero et al 30 published a case series that identified four breast implant-associated ALCL cases out of a total of 39 periprosthetic fluid samples. 30 They identified a statistically significant difference in the percentage of CD30-positive cells between breast implant-associated ALCL and those samples without tumor (54.3% in breast implant-associated ALCL vs. 0.3% in non-tumor; P = .03).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The submitting authors have hypothisized that the occurrence of BIA‐ALCL in Brazil is underreported, and therefore it is important to focus on this subject to better investigate this disease. In this report, the authors concluded that the application of FC with a comprehensive antibody panel consisting of CD30 in conjunction with CD25 and HLA‐DR can discriminate anaplastic cells of breast implant‐ associated anaplastic large cell lymphoma from lymphoid or neutrophilic reactive cells and should be considered in the initial evaluation of these lymphoma entities (De Azambuja et al, 2022; Debliquis et al, 2020; Wong‐Arteta et al, 2020).…”
mentioning
confidence: 99%
“…The submitting authors have hypothisized that the occurrence of BIA-ALCL in Brazil is underreported, and therefore it is important to focus on this subject to better investigate this disease. In this report, the authors concluded that the application of FC with a comprehensive antibody panel consisting of CD30 in conjunction with CD25 and HLA-DR can discriminate anaplastic cells of breast implantassociated anaplastic large cell lymphoma from lymphoid or neutrophilic reactive cells and should be considered in the initial evaluation of these lymphoma entities(De Azambuja et al, 2022;Debliquis et al, 2020;Wong-Arteta et al, 2020).CAR-T-cell therapy has been recently approved in United Statesand Europe for the treatment of several hematological malignancies, since it achieved impressive results in patients with relapsed/ refractory B-acute lymphocytic leukemia (B-ALL) and diffuse large B-cell lymphoma (DLBCL)(Johansson et al, 2021;Maryamchik et al, 2020;Sarikonda et al, 2020;Yu et al, 2022). However, an increasing body of evidence suggests that a sizeable proportion of patients treated with CAR-T cells do not experience a long-term response.…”
mentioning
confidence: 99%